The effect of financial incentives and task-specific cognitive abilities on task performance - Ondérej Rydval (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
We extend evidence on the interaction between financial incentives and cognitive abilities by focusing on the effect of task-specific abilities. In a memory-intensive task situated in an accounting context, the effect of accounting education on performance is stronger under financial incentives as compared to flat rate pay. Subjects with more accounting education respond stronger to financial incentives. Hence using incentives efficiently may involve targeting them at high-ability individuals. More generally, taking into account the incentive-ability interaction seems important when interpreting observed behavior in cognitively demanding lab and field economic environments.
Keywords: C81; C91; C93; D83; 330; financial incentives; cognitive ability; performance; experiment; Arbeitsleistung; Anforderungsprofil; Leistungsentgelt; Kognition; Test